Effectiveness of the Partnership Pattern of the Sumber Makmur Village Unit Cooperative (KUD) in Malang Regency in Improving Community Welfare - Afi Rachmad Slamet; Nur Hidayati (Innovation Business Management and Accounting Journal, 2022)
The purpose of this study was to determine the effectiveness of the implementation of the business partnership between the Sumber Makmur Village Unit Cooperative (KUD) and PT Hanjaya Mandala Sampoerna has been running effectively. This study also try to find out how the business partner relationship formed between the Sumber Makmur Village Unit Cooperative (KUD) and PT Hanjaya Mandala Sampoerna could develop business and improve community welfare in Ngantang, Malang Regency. Study focused on description about partnership implementation and what benefits are obtained from it. This type of research is descriptive qualitative research. The data collection method used is a system of observation, interviews, distribution questionnaires, and documentation. The population of this study are employees of Cigarette Production Partner (MPS) in Ngantang, while the number of respondents as a sample is employees who get direct benefits from the company. Data analysis uses data reduction, data presentation, and drawing conclusion. Result from this study reveal that there is reduced unemployment rate of the Ngantang community since the start of the factory construction, approximately 90% of MPS workers are local people. Another finding is about the existence of CSR funds can provide better education to the Ngantang community to respond to Natural Disasters, Fires, and the Environment in the form of reforestation, as well as help or reduce the cost of education for orphans. In general, partnership between KUD and HMS is able to increase the economic growth of the Ngantang community and its circumstances.